KARAKTERISTIK BUAH KAKAO YANG DIPANEN PADA BERBAGAI KETINGGIAN TEMPAT TUMBUH DAN KELAS KEMATANGAN - Nur Alam Nur Alam; Muhammad Salim Saleh; Gatot Siswo Hutomo (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The aim of the research was to determine the effect of altitude and cacao maturity class on cacao fruit characteristics and seed quality. Cacao fruits were harvested from three different altitudes  (first factor): 1-<400, >400-800 and >800 m above sea level (asl); and three different maturity classes (second): maturity class B (yellow on the fruit skin groove), maturity class A (yellow on the whole fruit skin surface) and maturity class A+ (dark yellow on the whole fruit skin surface).  Physical fruit characteristics were analysed on weight, fruit skin content, placenta, dental pulp, wet and dry seed yield, seed number/100 g, unfermented seed, and pulp content and its chemical components (sugar and total acid content).  The combination of the two factors resulted in  27 experimental units. The research resuts showed that cocoa fruit harvested from the plants growing at >400-900 m asl produced highest fruit weight (494.76 g), dry seed yield (8.43% dry weight) and seed size (90 seeds/100g).  Whereas at 1 - <400 m asl, the cacao fruit produced highest pulp sugar content (8.83%), lowest seed size (116 seeds/100 g) and unfermented seed (3.16%). Cacao fruit harvested from plant growing at >400 - <800 m asl with maturity class A produced seed which meet most the quality standard set by the SNI trade 01-2323-2002. The altitude as a growth factor is more dominant in influencing the cacao fruit characteristics than either the fruit maturity class or its combination with the altitude factor.